Impact of Low Skeletal Muscle Mass on Complications and Survival for Gastric Cancer: A Propensity Score Matching Analysis - Fang, Zhen; Shang, Liang; Li, Leping (Frontiers in Surgery, 2022)
Background: Cancer is a major disease burden to society. Increasing evidence has indicated that low skeletal muscle mass is linked with cancer prognosis. The purpose of the study is to determine the impact of preoperative low skeletal muscle mass (LSMM) on complications and survival of patients who undergo laparoscopic gastrectomy for gastric cancer (GC). Methods: This study retrospectively collected patients undergoing laparoscopic gastrectomy for GC between January 2017 and December 2018. Tumor staging was performed according to the American Joint Committee on Cancer 8th edition. The third lumbar psoas index (PMI) was assessed by computed tomography (CT) within 15 days before surgery. Postoperative complications were classified according to Clavien-Dindo classification and dichotomized into none vs any (Clavien-Dindo score, ≥1). Using propensity score matching (1:1) to obtain 2 well-balanced cohorts for available variables influencing clinical outcomes, comparing the postoperative complications and 3-year overall survival (OS) between LSMM group and non-LSMM group. Results: A total of 386 patients, 226 were matched for analyses. The average patient age was 57.31±10.33 years; 75.65% (n = 292) were men and 24.35% (n = 94) were women. A total of 249 (64.51%) patients were diagnosed with LSMM. Compared with the non-LSMM group, the LSMM group manifested significantly shorter 3-year OS (58.14% vs 71.95%, P=0.034). However, the incidence of postoperative complications was no difference between two groups after matching. After stratification based on the pT stage of the tumor, statistically significant difference in the 3-year OS rates of the advance GC cohort between the two groups were observed. Conclusions: LSMM predicts a poor prognosis for patients with advance GC and it is not associated with postoperative complications.